(untitled) (Fiep Bulletin - online, 2014)
This research had the purpose to analyze the level of general motor control of 35 female subjects over 60 years of age enrolled at the ULBRATI Program at ULBRA, Canoas, RS in 2005 chosen through a convenience method of sampling. In this descriptive study it was used the Rosa Neto´s Elderly Motor Scale (2002) that assesses the basic motor elements such as fine motor coordination, general coordination, balance, body scheme, space and time organization. The study showed that among the sample subjects, 91.4% was classified as very low and 8.6% as low in the assessment scale. It was observed that the average age level was 69.49 while the general motor control presented an average value of 47.66 and it was classified as very low in the scale. It was shown that in the motor parameters average the subjects were classified as very low in the scale while in the space organization variable they achieved the scale low classification. When data were submitted to the Pearson´s correlation coefficient it was observed a significant inverted correlation between chronological age and general motor control. It was concluded that the subjects´low level of general motor control observed can interfere in the elderly motor capacity while doing activites of daily life and harm their quality of life.